Development of E-Supplement Teaching Materials Physics Based On Flipbook in Balogo Traditional Games - Nadhiroh, Afifah Khansa (Universitas Veteran Bangun Nusantara, 2022)
Indonesia is a country rich in cultural diversity that is spread in every region, one of which is traditional games. The existence of traditional game from time to time began to eroded and forgotten among children. Along with the development of the times, educators must follow the development of existing technology and not forget the cultural values of the local area. The existence of traditional games can be maintained by introducing and integrating them into learning through teaching materials. Therefore, this research is focused on the development of e-suplement teaching materials physics based on flipbook in balogo traditional games. This research aim to determine the validity and feasibility of e-suplement teaching materials physics based on flipbook in balogo traditional games. This research uses the research and development method od 3D models (define, design and develop) modified Thiagarajan’s 4D models. The results of research indicates that e-suplement teaching materials physics based on flipbook in balogo traditional games is very good with validity 91,36%. The concluded is e-suplement teaching materials physics based on flipbook in balogo traditional games valid and very feasible for use in learning.